SANKSI KEBIRI KIMIA DALAM UNDANG-UNDANG PERLINDUNGAN ANAK DI INDONESIA PERSPEKTIF HUKUM POSITIF DAN HUKUM PROGRESIF - Faqih Zuhdi Rahman (Semarang Law Review (SLR), 2025)
The presence of a civil law system derived from written law is adjusted to the conditions of a society in a state of law. the development of the dynamics of life gives rise to the latest products in legal life, one of which is the chemical castration sanction for cases of sexual violence, only this has not been written and included in the Criminal Code. This type of research uses normative juridical research. The author intends to explore further the chemical castration sanction in Indonesia based on the perspective of positive law and progressive law. The results of the study explain that within the scope of positive law, chemical castration can be implemented as a punishment for perpetrators of sexual crimes, which is textually stated in Law No. 17 of 2016. In the analysis of progressive law, responding to chemical castration sanctions can be seen more critically. Progressive law encourages things like psychological rehabilitation, education and social reintegration, taking into account protection for victims.   Abstrak Hadirnya sistem hukum civil law yang berasal dari hukum tertulis disesuaikan oleh kondisi suatu masyarakat dalam sebuah negara hukum. perkembangan dinamika kehidupan memunculkan produk terbaru dalam kehidupan hukum salah satunya sanksi kebiri bagi kasus tindak pidana kekerasan seksual, hanya saja hal ini belum tertulis dan dicantumkan dalam KUHP. Jenis penelitian ini menggunakan penelitian yuridis normative. Penulis bermaksud menelusuri lebih jauh mengenai sanksi kebiri kimia di Indonesia berdasarkan perspektif hukum positif dan hukum progresif. Hasil penelitian menjelaskan dalam ruang lingkup hukum positif kebiri kimia dapat diimplementasikan untuk hukuman bagi pelaku kejahatan seksual, yang secara tekstual tertuang dalam UU No. 17 Tahun 2016. Dalam analisa hukum progresif menanggapi sanksi kebiri kimia dapat terlihat lebih kritis. Hukum progresif mendorong pada hal seperti rehabilitasi psikologis, pendidikan dan reintegrasi sosial, dengan mempertimbangkan perlindungan untuk korban.